2020
DOI: 10.1002/phar.2438
|View full text |Cite
|
Sign up to set email alerts
|

Baricitinib: A Review of Pharmacology, Safety, and Emerging Clinical Experience in COVID‐19

Abstract: A hyperinflammatory response to severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) infection, reminiscent of cytokine release syndrome, has been implicated in the pathophysiology of acute respiratory distress syndrome and organ damage in patients with coronavirus disease 2019 (COVID‐19). Agents that inhibit components of the pro‐inflammatory cascade have garnered interest as potential treatment options with hopes that dampening the proinflammatory process may improve clinical outcomes. Baricitinib is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 64 publications
(175 reference statements)
6
179
2
11
Order By: Relevance
“…remdesivir) and other drugs [38]. However, the use of baricitinib is associated with increased thromboembolic events, which is concerning given that COVID-19 patients are at risk of developing these events [39].…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…remdesivir) and other drugs [38]. However, the use of baricitinib is associated with increased thromboembolic events, which is concerning given that COVID-19 patients are at risk of developing these events [39].…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%
“…remdesivir) and other drugs [ 38 ]. However, the use of baricitinib is associated with increased thromboembolic events, which is concerning given that COVID-19 patients are at risk of developing these events [ 39 ]. In an Italian open-label study of 12 patients with moderate COVID-19 pneumonia [ 40 ], baricitinib therapy combined with lopinavir/ritonavir was associated with significant improvement in clinical and laboratory parameters, and none of the patients required intensive care unit support, however, the study was limited by its small sample size and open-label design.…”
Section: Specific Immune Modulatorsmentioning
confidence: 99%
“…The side effects like headache, upper respiratory tract infection (UTI), nasopharyngitis are commonly seen in patients with Baricitinib therapy. The long term use of Baricitinib may increase the risks of developing serious infections and thromboembolic events in patients [ 112 ]. Consumption of Immunosuppressants concomitantly with Baricitinib was more likely prone to these infections.…”
Section: Possible Side Effects Of Drugs Altering the Jak-stat Signalimentioning
confidence: 99%
“…NCT04340232, NCT04358614, NCT04345289, NCT04399798, NCT04320277). These trials will also address safety concerns related to the reported increase in thromboembolic events associated with JAK inhibitors which may further increase the hypercoagulability risk inherent to COVID-19 ( Jorgensen et al, 2020 ; Tang Y. et al, 2020 ).…”
Section: Tumor Necrosis Factor and Janus Kinasesmentioning
confidence: 99%